How do manufacturing enterprises construct e-commerce platforms for sustainable development? A case study of resource orchestration - Hu, Jingbo; Ouyang, Taohua; Wei, William Xiaojun; Cai, Jiawei (My University, 2020)
The existing literatures mainly focus on the pricing, strategic significance and sustainable development characteristics of the e-commerce platform, and lack deep research on mechanisms in the process of construction like main structure of recourses and driving force. This paper takes Haier as a Chinese example and explores how manufacturing enterprises create and develop the sustainable e-commerce platform. The research findings show that: (1) An e-commerce platform respectively carries the functions of sales channels, service differences and innovation incubation in different stages of the manufacturing enterprises’ sustainable development; (2) For managing e-commerce platform of manufacturing enterprises’ sustainable development, resource orchestration can effectively realize the integration of value creation and resource; (3) Finally, it further reveals that the driving power which resource orchestration continuously promotes for the sustainable e-commerce platforms to construct is from the co-creation value of manufacturers and users. This paper discusses the structure of e-commerce platforms based on the main characteristics of each resource, and systematically explores the mechanism and evolutionary driving force of resource orchestration to promote the construction of e-commerce platforms for the sustainable development. It complements and enriches the innovation ecosystem and resource orchestration theory, providing significant practical guidance to the sustainable development of manufacturing enterprises.
Keywords: e-commerce platform; resource orchestration; sustainable development; construction mechanism